Depending the Structure and Optical Properties of Cadmium Telluride Films on the Doping process - Iman hameed khudayer (Al-Mustansiriyah Journal of Science)
The purpose of the present paper is to study the effect of doping by different materials on the structure and the optical properties of Cadmium Telluride films which prepared by rate deposition (4.21 nmn/sec) and thickness (≈ 200 nm) in vacuum by use thermal evaporation technique at a substrate temperature (300K), we are studying the effect of doping by different material (Antimony, Aluminum and Silver) on the structural1and optical2 properties of CdTe thin films. The structural properties of these films have been studied by using X-ray diffraction methods. The optical measurements indicated that Cadmium Telluride films have a direct optical energy gap (Egopt), and it decreases when we doped this films by different materials (Sb, Al and Ag) with the same ratio doping. The optical constants refractive index (n), extinction coefficient (k), absorption coefficient (α) and dielectric constants (r and i) were also studied.